A comb-shaped polymer, its preparation method and application

By using a comb polymer composed of olefinic reactive polyether, N-vinylpyrrolidone, olefinic polymerizable anhydride and primary amino ring compound as a dispersant, the carbon nanotube slurry caused by the traditional PVPK series dispersant is solved The problems of high viscosity, poor fluidity and poor storage stability are achieved by achieving better dispersion performance and stability.

CN115975126BActive Publication Date: 2025-01-24SHANGHAI YUKING WATER SOLUBLE MATERIAL TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211675439.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-26
Publication Date
2025-01-24
Estimated Expiration
2042-12-26

AI Technical Summary

Technical Problem

The traditionally used PVPK series carbon nanotube slurry as dispersants have problems such as high slurry viscosity, poor fluidity and poor storage stability, which leads to a decrease in the quality of carbon nanotube slurry and affects battery performance.

Method used

Combs composed of hypertrophic polyether, N-ethylene pheumidone, olenic anhydride, and bibamide base ring compounds are used as dispersers. Comb polymer.

Benefits of technology

It significantly improves the decentralized performance of carbon nanotinal pulp, with small particle size, low viscosity, good liquidity, and the storage stability of the slurry after a long time is good, maintaining high quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure BDA0004016946700000023
    Figure BDA0004016946700000023
Patent Text Reader

Abstract

The invention discloses a comb-type polymer and a preparation method and application thereof, wherein the comb-type polymer is composed of an olefinic active polyether, N-vinyl pyrrolidone, an olefinic polymerizable anhydride and a primary amino ring compound. The preparation method comprises: adding an olefinic active polyether and a solvent to a reaction vessel, heating and stirring until the olefinic active polyether is fully dissolved; dissolving an olefinic polymerizable anhydride and an initiator in a solvent respectively, dropping N-vinyl pyrrolidone, an olefinic polymerizable anhydride solution and an initiator solution of 80% by mass into the above-mentioned reaction vessel simultaneously, dropping is completed, and after the reaction is kept warm for 1-10 hours, the remaining 20% ​​by mass of the initiator solution is added dropwise, and the initiator solution is kept warm for 1-5 hours to obtain an intermediate; the above-mentioned materials are heated to 100-150°C, a primary amino ring compound is added, and the temperature is kept warm for 1-10 hours, and the acid value is detected to judge the reaction end point, and the comb-type polymer is cooled to obtain the carbon nanotube slurry prepared by the comb-type polymer as a dispersant, and the carbon nanotube slurry has good dispersibility, low viscosity and good fluidity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new materials and chemical engineering, and in particular to a comb-type polymer and a preparation method and application thereof. Background Art

[0002] Carbon nanotubes are a one-dimensional quantum nanomaterial with a special structure. They are light in weight, have perfectly linked hexagonal structures, and have many excellent mechanical, electrical, and chemical properties. With the development of research on the application of carbon nanotubes, the outstanding performance of carbon nanotubes in the application of positive electrode materials for lithium batteries has been widely recognized. The addition of carbon nanotubes can ensure that the battery has good charge and discharge performance. In addition, carbon nanotubes as conductive agents can also improve the charge and discharge efficiency and the service life of lithium batteries. As an emerging conductive agent, carbon nanotubes have a conductive network that is different from traditional conductive agents, which can better improve the conductive properties of motor materials, thereby reducing the amount of conductive agent added and increasing the content of active substances.

[0003] When carbon nanotubes are used, they are usually ground into a nanoscale flowable slurry, namely carbon nanotube slurry. This allows carbon nanotubes to be used in the preparation of battery positive electrode slurry to give full play to the superior properties of the material itself. When preparing carbon nanotube slurry, the traditional dispersing material used is polyvinyl pyrrolidone (PVP), mainly PVPK20-40 (PVP with different molecular weights is represented by PVPKn, where Kn represents the average molecular weight of PVP is n×10 3 ), but the carbon nanotube slurry using PVPK series as dispersant not only has high slurry viscosity and poor fluidity, but also poor storage stability. If the slurry is placed for a long time, the dispersion medium will precipitate, resulting in a decrease in the quality of the carbon nanotube slurry, which in turn affects the performance of the battery. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a comb-type polymer with better dispersion performance and a preparation method and application thereof.

[0005] The first object of the present invention is to provide a comb-type polymer, wherein the comb-type polymer is composed of polymerization units of olefinic active polyether a, N-vinyl pyrrolidone b, olefinic polymerizable acid anhydride c, and primary amino ring compound d;

[0006] The weight average molecular weight of the comb-type polymer is 50000-100000 g / mol, and the molar ratio of the polymer units a, b, c, and d is (0.1-0.5): (2.0-10.0): (0.4-2.0): (0.4-2.0), wherein d≤c; preferably, the molar ratio of the polymer units c and d is 1, and the molar relationship ratio of the polymer units a, b, and c is

[0007] Further, the olefinic reactive polyether has the following general formula:

[0008]

[0009] Wherein: R1, R2, R3 are H-, CH3-, or CH3CH2-; m, n≥0, m, n are both integers, and 10≤m+n≤100, preferably, controlled within 40≤m+n≤70, n≥m.

[0010] Furthermore, the olefinic polymerizable anhydride is maleic anhydride, itaconic anhydride, or citraconic anhydride; and the primary amino ring compound is cyclohexylamine, 2-phenoxyaniline, naphthylamine, or 5-aminopyridine.

[0011] A second object of the present invention is to provide a method for preparing the comb polymer, comprising the following steps:

[0012] (1) adding an olefinic active polyether and a solvent into a reaction vessel, heating the vessel to 50-100° C., and stirring the vessel until the olefinic active polyether is fully dissolved;

[0013] (2) dissolving an olefinic polymerizable anhydride and an initiator in a solvent to prepare an olefinic polymerizable anhydride solution and an initiator solution, respectively, and simultaneously dropping N-vinyl pyrrolidone, the olefinic polymerizable anhydride solution and 80% by weight of the initiator solution into the reaction vessel of step (1), slowly dropping the three in 0.5-5.0 hours, keeping the temperature for reaction for 1-10 hours, dropping the remaining 20% ​​by weight of the initiator solution, and continuing to keep the temperature for 1-5 hours to obtain an intermediate;

[0014] (3) The material in step (2) is heated to 100-150° C., a primary amino ring compound is added, and the reaction is carried out at the temperature for 1-10 hours. When the acid value is detected to be less than 5 mgKOH / g, the reaction is terminated and the temperature is lowered to obtain a comb-type polymer.

[0015] Furthermore, in the step (1), the mass ratio of the olefinic active polyether to the solvent is 1:1 to 1:3.

[0016] Furthermore, in the step (2), the amount of the initiator added is 0.1% to 2.0% of the total mass of the olefinic active polyether, N-vinyl pyrrolidone and the olefinic polymerizable anhydride, preferably, controlled at 0.1% to 0.5%.

[0017] Furthermore, in the step (2), in the initiator solution, the mass ratio of the initiator to the solvent is 0.01:1 to 0.02:1; and in the olefinic polymerizable anhydride solution, the mass ratio of the olefinic polymerizable anhydride to the solvent is 0.15:1 to 0.25:1.

[0018] Furthermore, the initiator in step (2) is an azo free radical initiator or a peroxide free radical initiator, the azo free radical initiator is any one of azobisisobutyronitrile and azobisisoheptanenitrile; the peroxide free radical initiator is benzoyl peroxide.

[0019] Furthermore, the solvent in step (1) and step (2) is the same, and the solvent is one of N-methylpyrrolidone and N-ethylpyrrolidone.

[0020] The third object of the present invention is to provide the use of the comb polymer in the dispersion of carbon nanotube slurry.

[0021] The beneficial effects of the present invention are as follows:

[0022] The polymerized units of the comb-type polymer of the present invention are composed of olefinic active polyether, N-vinyl pyrrolidone, olefinic polymerizable acid anhydride and primary amino ring compound, wherein the olefinic active polyether, N-vinyl pyrrolidone and olefinic polymerizable acid anhydride undergo free radical polymerization reaction, and the primary amino ring compound undergoes imidization ring-closing reaction with acid anhydride on the basis of the product of the free radical polymerization reaction to form the final comb-type polymer.

[0023] The dispersibility of the comb-type polymer in carbon nanotubes is better than that of the traditional dispersing material PVK30. The carbon nanotube slurry prepared by using the comb-type polymer as a dispersant not only has a small particle size, low viscosity and good fluidity, but also has good storage stability and stable quality after being placed for a long time. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] In the examples of the present invention, the weight average molecular weight is measured by gel permeation chromatography (GPC) using polyethylene oxide as a calibration standard and a water / acetonitrile mixed solution as an eluent.

[0026] Example 1. Preparation of comb polymer

[0027] (1) Add 96.0 g (0.04 mol) of allyl polyethylene glycol (APEG2400) and 96 g of N-methylpyrrolidone solvent to a reaction vessel equipped with condensation reflux, nitrogen protection, stirring device and constant pressure funnel, raise the temperature to 60° C. and stir until APEG2400 is completely dissolved.

[0028] (2) dissolving 15.7 g (0.16 mol) of maleic anhydride in 85.0 g of N-methylpyrrolidone to prepare a maleic anhydride solution, and dissolving 0.4 g of azobisisobutyronitrile as an initiator in 32.0 g of N-methylpyrrolidone to prepare an initiator solution;

[0029] 88.9 g (0.8 mol) of N-vinyl pyrrolidone, maleic anhydride solution and 25.9 g of 80% initiator solution were simultaneously added dropwise to the reaction vessel of step (1) through a constant pressure funnel, and the addition of the three was completed within 2.0 hours. After keeping the temperature for reaction for 3.0 hours, the remaining 6.5 g of 20% initiator solution was added dropwise, and the temperature was kept for reaction for 1 hour to obtain intermediate 1.

[0030] (3) The material in step (2) was heated to 120° C., 22.9 g (0.16 mol) of naphthylamine was added, and the mixture was kept warm for 4 hours. When the acid value was less than 5 mg KOH / g, the reaction was terminated to obtain a comb-type polymer 1, which had a weight average molecular weight of 88420 g / mol.

[0031] Example 2: Preparation of comb polymer

[0032] (1) Add 96.0 g (0.04 mol) of methyl allyl polyethylene glycol (HPEG2400) and 144 g of N-methylpyrrolidone solvent to a reaction vessel equipped with condensation reflux, nitrogen protection, stirring device and constant pressure funnel, raise the temperature to 65° C. and stir until HPEG2400 is completely dissolved.

[0033] (2) dissolving 9.0 g (0.08 mol) of itaconic anhydride in 54.0 g of N-methylpyrrolidone to prepare an itaconic anhydride solution, and dissolving 0.5 g of azobisisoheptanenitrile as an initiator in 35.0 g of N-methylpyrrolidone to prepare an initiator solution;

[0034] 66.7 g (0.6 mol) of N-vinyl pyrrolidone, itaconic anhydride solution and 28.4 g of 80% initiator solution were simultaneously added dropwise to the reaction vessel of step (1) through a constant pressure funnel, and the addition of the three was ensured to be completed within 4.0 hours. After keeping the temperature for reaction for 4.0 hours, the remaining 7.1 g of 20% initiator solution was added dropwise, and the temperature was kept for reaction for 2 hours to obtain intermediate 2.

[0035] (3) The material in step (2) was heated to 140° C., 7.9 g (0.08 mol) of cyclohexylamine was added, and the mixture was kept warm for 6 hours. When the acid value was less than 5 mg KOH / g, the reaction was terminated to obtain a comb-type polymer 2, whose weight average molecular weight was measured to be 65751 g / mol.

[0036] Example 3. Preparation of comb polymer

[0037] (1) Add 100.0 g (0.05 mol) of methyl allyl polyethylene glycol (HPEG2000) and 200 g of N-methylpyrrolidone solvent to a reaction vessel equipped with condensation reflux, nitrogen protection, stirring device and constant pressure funnel, heat to 75° C. and stir until HPEG2000 is completely dissolved.

[0038] (2) dissolving 14.7 g (0.15 mol) of maleic anhydride in 85.0 g of N-methylpyrrolidone to prepare a maleic anhydride solution, and dissolving 1.1 g of benzoyl peroxide as an initiator in 80.0 g of N-methylpyrrolidone to prepare an initiator solution;

[0039] 100.0 g (0.9 mol) of N-vinyl pyrrolidone, maleic anhydride solution and 64.9 g of 80% initiator solution were simultaneously added dropwise to the reaction vessel of step (1) through a constant pressure funnel, and the addition of the three was ensured to be completed within 1.0 hour. After keeping the temperature for reaction for 5.0 hours, the remaining 16.2 g of 20% initiator solution was added dropwise, and the temperature was kept for reaction for 4 hours to obtain intermediate 3.

[0040] (3) The material in step (2) was heated to 140° C., 14.3 g (0.15 mol) of 5-aminopyridine was added, and the mixture was kept warm for 6 hours. When the acid value was less than 5 mg KOH / g, the reaction was terminated to obtain a comb-type polymer 3, whose weight average molecular weight was measured to be 59182 g / mol.

[0041] Example 4. Preparation of comb polymer

[0042] (1) Add 100.0 g (0.05 mol) of allyl polyethylene glycol (APEG2000) and 150 g of N-methylpyrrolidone solvent to a reaction vessel equipped with condensation reflux, nitrogen protection, stirring device and constant pressure funnel, heat to 85° C. and stir until APEG2000 is completely dissolved.

[0043] (2) dissolving 21.3 g (0.19 mol) of citraconic anhydride in 117.0 g of N-methylpyrrolidone to prepare a citraconic anhydride solution, and dissolving 1.2 g of benzoyl peroxide as an initiator in 75.0 g of N-methylpyrrolidone to prepare an initiator solution;

[0044] 111.0 g (1.0 mol) of N-vinyl pyrrolidone, citraconic anhydride solution and 53.3 g of 80% initiator solution were simultaneously added dropwise to the reaction vessel of step (1) through a constant pressure funnel, and the addition of the three was ensured to be completed within 1.5 hours. After keeping the temperature for 9.0 hours, the remaining 20% ​​initiator solution (22.9 g) was added dropwise, and the temperature was kept for 2 hours to obtain intermediate 4.

[0045] (3) The material in step (2) was heated to 145° C., 35.2 g (0.19 mol) of 2-phenoxyaniline was added, and the mixture was kept warm for 8 hours. When the acid value was less than 5 mg KOH / g, the reaction was terminated to obtain a comb-type polymer 4, whose weight average molecular weight was measured to be 91345 g / mol.

[0046] Example 5. Preparation of comb polymer

[0047] (1) Add 72.0 g (0.03 mol) of allyl polyethylene glycol (APEG2400) and 72 g of N-methylpyrrolidone solvent to a reaction vessel equipped with condensation reflux, nitrogen protection, stirring device and constant pressure funnel, raise the temperature to 80° C. and stir until APEG2400 is completely dissolved.

[0048] (2) dissolving 7.8 g (0.08 mol) of maleic anhydride in 47.0 g of N-methylpyrrolidone to prepare a maleic anhydride solution, and dissolving 0.7 g of azobisisobutyronitrile as an initiator in 50.0 g of N-methylpyrrolidone to prepare an initiator solution;

[0049] 55.6 g (0.5 mol) of N-vinyl pyrrolidone, maleic anhydride solution and 40.6 g of 80% initiator solution were simultaneously added dropwise to the reaction vessel of step (1) through a constant pressure funnel, and the addition of the three was ensured to be completed within 5.0 hours. After keeping the temperature for reaction for 9.0 hours, the remaining 10.1 g of 20% initiator solution was added dropwise, and the temperature was kept for reaction for 3 hours to obtain intermediate 5.

[0050] (3) The material in step (2) was heated to 110° C., 14.8 g (0.08 mol) of 2-phenoxyaniline was added, and the mixture was kept warm for 3 hours. When the acid value was less than 5 mg KOH / g, the reaction was terminated to obtain a comb-type polymer 5, whose weight average molecular weight was measured to be 54519 g / mol.

[0051] Example 6. Preparation of comb polymer

[0052] The preparation method of this embodiment is basically the same as that of embodiment 1, except that: in step (3), the material is heated to 140°C, 15.9 g (0.16 mol) of cyclohexylamine is added, and the reaction is kept warm for 8 hours. When the acid value is less than 5 mgKOH / g, the reaction is terminated to obtain a comb-type polymer 6, and its weight average molecular weight is measured to be 87319 g / mol.

[0053] Example 7. Preparation of comb polymer

[0054] The preparation method of this embodiment is basically the same as that of Example 2, except that: in step (3), the material is heated to 130°C, 14.8g (0.08mol) of 2-phenoxyaniline is added, and the reaction is kept warm for 4 hours. When the acid value is less than 5mgKOH / g, the reaction is terminated to obtain a comb-type polymer 7, and its weight average molecular weight is measured to be 66472g / mol.

[0055] Example 8. Preparation of comb polymer

[0056] (1) Add 48.0 g (0.02 mol) of allyl polyethylene glycol (APEG2400) and 48.0 g of N-ethylpyrrolidone solvent to a reaction vessel equipped with condensation reflux, nitrogen protection, stirring device and constant pressure funnel, raise the temperature to 50° C. and stir until APEG2400 is completely dissolved.

[0057] (2) dissolving 3.9 g (0.04 mol) of maleic anhydride in 26.0 g of N-ethylpyrrolidone to prepare a maleic anhydride solution, and dissolving 0.4 g of benzoyl peroxide as an initiator in 17.5 g of N-ethylpyrrolidone to prepare an initiator solution;

[0058] 22.2 g (0.2 mol) of N-vinyl pyrrolidone, maleic anhydride solution and 14.3 g of 80% initiator solution were simultaneously added dropwise to the reaction vessel of step (1) through a constant pressure funnel, and the addition of the three was ensured to be completed within 5.0 hours. After keeping the temperature for 1.0 hour, the remaining 3.6 g of 20% initiator solution was added dropwise, and the temperature was kept for 5 hours to obtain intermediate 8.

[0059] (3) The material in step (2) was heated to 100° C., 3.8 g (0.04 mol) of 5-aminopyridine was added, and the reaction was kept warm for 1 hour. When the acid value was less than 5 mgKOH / g, the reaction was terminated to obtain a comb-type polymer 8, whose weight average molecular weight was measured to be 59781 g / mol.

[0060] Example 9: Preparation of comb polymer

[0061] (1) In a reaction vessel equipped with condensation reflux, nitrogen protection, stirring device and constant pressure funnel, 24.0 g (0.01 mol) of allyl polyethylene glycol (APEG2400) and 72.0 g of N-ethylpyrrolidone solvent were added, the temperature was raised to 100° C. and stirred until APEG2400 was completely dissolved.

[0062] (2) dissolving 22.4 g (0.2 mol) of itaconic anhydride in 89.0 g of N-ethylpyrrolidone to prepare an itaconic anhydride solution, and dissolving 0.15 g of azobisisobutyronitrile as an initiator in 15.0 g of N-ethylpyrrolidone to prepare an initiator solution;

[0063] 100.0 g (0.9 mol) of N-vinyl pyrrolidone, itaconic anhydride solution and 12.1 g of 80% initiator solution were simultaneously added dropwise to the reaction vessel of step (1) through a constant pressure funnel, and the addition of the three was completed within 0.5 hour. After keeping the reaction warm for 10.0 hours, the remaining 3.05 g of 20% initiator solution was added dropwise, and the reaction was kept warm for 1 hour to obtain intermediate 9.

[0064] (3) The material in step (2) was heated to 150° C., 19.8 g (0.2 mol) of cyclohexylamine was added, and the mixture was kept warm for 10 hours. When the acid value was less than 5 mg KOH / g, the reaction was terminated to obtain a comb-type polymer 9, which had a weight average molecular weight of 88590 g / mol.

[0065] Example 10, dispersion performance test:

[0066] The comb polymers 1-9 prepared in Examples 1-9 were used as dispersants to disperse carbon nanotubes. After dispersion, the particle size and viscosity of the carbon nanotube slurry were tested, as well as its accelerated stability at 55°C after 48 hours. PVPK30 commonly used on the market was used as a control.

[0067] Dispersion method: 8 parts of carbon nanotubes, 0.8 parts of dispersant and 91.2 parts of N-methylpyrrolidone were placed in a grinding cylinder and stirred at a speed of 1500 rpm for 2 hours to obtain a pre-dispersion liquid. The pre-dispersion liquid was then ground in a sand grinder for 4 hours and filtered to obtain a carbon nanotube slurry.

[0068] The performance of the carbon nanotube slurry was tested. The particle size of the slurry was detected by a BT-90 laser particle size analyzer, and the viscosity of the slurry was detected by a rotational viscometer. The stability of the slurry was observed after being placed in a constant temperature forced air drying oven at 55°C for 48 hours. The test results are shown in Table 1.

[0069] Table 1 Performance test results of carbon nanotube slurry

[0070] serial number Dispersants <![CDATA[Slurry particle size / D 50 > Viscosity / mpa·s 55℃、48h Example 1 Comb polymer 1 586 1153 Evenly dispersed Example 2 Comb polymer 2 315 791 Evenly dispersed Example 3 Comb polymer 3 416 936 Evenly dispersed Example 4 Comb polymer 4 389 812 Evenly dispersed Example 5 Comb polymer 5 515 1052 Evenly dispersed Example 6 Comb polymer 6 365 879 Evenly dispersed Example 7 Comb polymer 7 425 925 Evenly dispersed Example 8 Comb polymer 8 456 937 Evenly dispersed Example 9 Comb polymer 9 509 1056 Evenly dispersed Comparison PVK30 785 2156 Solvent precipitates from the upper layer

[0071] From the results in Table 1, it can be seen that the carbon nanotube slurry using the comb-type polymers 1-9 as dispersants prepared by the methods of Examples 1-9 has a particle size and viscosity significantly lower than that of the control PVK30, and after standing at 55°C for 48 hours, the carbon nanotube slurry using the comb-type polymers 1-9 as dispersants is still uniformly dispersed, while the carbon nanotube slurry using PVK30 as a dispersant has solvent precipitated from the upper layer of the slurry after standing for 48 hours. It can be seen that the dispersion performance of the comb-type polymer of the present invention in the carbon nanotube slurry is significantly better than that of the traditional dispersant PVK30.

[0072] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention are included in the protection scope of the present invention.

Claims

1. A comb polymer, characterized in that The comb-type polymer is composed of polymerization units of olefinic active polyether a, N-vinyl pyrrolidone b, olefinic polymerizable acid anhydride c, and primary amino ring compound d; The weight average molecular weight of the comb-type polymer is 50,000-100,000 g / mol, and the molar ratio of the polymer units a, b, c, and d is (0.1-0.5): (2.0-10.0): (0.4-2.0): (0.4-2.0), wherein d≤c; The olefinic active polyether, N-vinyl pyrrolidone and olefinic polymerizable acid anhydride undergo free radical polymerization reaction, and the primary amino ring compound and the acid anhydride undergo imidization ring-closing reaction to form the comb-type polymer.

2. The comb polymer according to claim 1, characterized in that The olefinically active polyether has the following general formula: ; Wherein: R1, R2, R3 are H-, CH3-, or CH3CH2-; m, n≥0, m, n are both integers, and 10≤m+n≤100.

3. The comb polymer according to claim 1, characterized in that The olefinic polymerizable anhydride is maleic anhydride, itaconic anhydride, or citraconic anhydride; the primary amino ring compound is cyclohexylamine, 2-phenoxyaniline, naphthylamine, or 5-aminopyridine.

4. The method for preparing a comb polymer according to any one of claims 1 to 3, comprising the following steps: (1) Adding an olefinic active polyether and a solvent into a reaction vessel, heating the vessel to 50-100° C., and stirring the vessel until the olefinic active polyether is fully dissolved; (2) dissolving an olefinic polymerizable acid anhydride and an initiator in a solvent respectively to obtain an olefinic polymerizable acid anhydride solution and an initiator solution, and simultaneously dropping N-vinyl pyrrolidone, the olefinic polymerizable acid anhydride solution and 80% by weight of the initiator solution into the reaction vessel of step (1), slowly dropping the three into the reaction vessel over a period of 0.5-5.0 hours, and after keeping the temperature for reaction for 1-10 hours, dropping the remaining 20% ​​by weight of the initiator solution, and continuing to keep the temperature for 1-5 hours to obtain an intermediate; (3) The material in step (2) is heated to 100-150° C., a primary amino ring compound is added, and the reaction is kept warm for 1-10 hours. When the acid value is detected to be less than 5 mgKOH / g, the reaction is terminated and the temperature is lowered to obtain a comb-type polymer.

5. The preparation method according to claim 4, characterized in that: In the step (1), the mass ratio of the olefinic active polyether to the solvent is 1:1 to 1:

3.

6. The preparation method according to claim 4, characterized in that: In the step (2), the amount of the initiator added is 0.1% to 2.0% of the total mass of the olefinic active polyether, N-vinyl pyrrolidone and the olefinic polymerizable anhydride.

7. The preparation method according to claim 4, characterized in that: In the step (2), in the initiator solution, the mass ratio of the initiator to the solvent is 0.01:1 to 0.02:1; and in the olefinic polymerizable anhydride solution, the mass ratio of the olefinic polymerizable anhydride to the solvent is 0.15:1 to 0.25:

1.

8. The preparation method according to claim 4, characterized in that: The initiator in step (2) is an azo free radical initiator or a peroxide free radical initiator. The azo free radical initiator is any one of azobisisobutyronitrile and azobisisoheptanenitrile; the peroxide free radical initiator is benzoyl peroxide.

9. The preparation method according to claim 4, characterized in that: The solvent in step (1) and step (2) is the same, and the solvent is one of N-methylpyrrolidone and N-ethylpyrrolidone.

10. Use of the comb polymer according to any one of claims 1 to 3 in the dispersion of carbon nanotube slurry.

Citation Information

Patent Citations

  • CNT (carbon nano tube) dispersant and preparation method thereof

    CN108102041A

  • Dispersing agent, preparation method and application of dispersing agent in preparation of carbon nanotube dispersion liquid

    CN115322293A